M Phase Phosphoprotein 10 Is a Human U3 Small Nucleolar Ribonucleoprotein Component - Westendorf, Joanne M. (The American Society for Cell Biology, 1998)
We have previously developed a novel technique for isolation of cDNAs encoding M phase phosphoproteins (MPPs). In the work described herein, we further characterize MPP10, one of 10 novel proteins that we identified, with regard to its potential nucleolar function. We show that by cell fractionation, almost all MPP10 was found in isolated nucleoli. By immunofluorescence, MPP10 colocalized with nucleolar fibrillarin and other known nucleolar proteins in interphase cells but was not detected in the coiled bodies stained for either fibrillarin or p80 coilin, a protein found only in the coiled body. When nucleoli were separated into fibrillar and granular domains by treatment with actinomycin D, almost all the MPP10 was found in the fibrillar caps, which contain proteins involved in rRNA processing. In early to middle M phase of the cell cycle, MPP10 colocalized with fibrillarin to chromosome surfaces. At telophase, MPP10 was found in cellular structures that resembled nucleolus-derived bodies and prenucleolar bodies. Some of these bodies lacked fibrillarin, a previously described component of nucleolus-derived bodies and prenucleolar bodies, however, and the bulk of MPP10 arrived at the nucleolus later than fibrillarin. To further examine the properties of MPP10, we immunoprecipitated it from cell sonicates. The resulting precipitates contained U3 small nucleolar RNA (snoRNA) but no significant amounts of other box C/D snoRNAs. This association of MPP10 with U3 snoRNA was stable to 400 mM salt and suggested that MPP10 is a component of the human U3 small nucleolar ribonucleoprotein.